2018
DOI: 10.3390/antibiotics7040102
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Global Research on Clavulanic Acid

Abstract: Clavulanic acid (CA), a potent inhibitor of the β-lactam, ase enzyme, is frequently co-formulated with a broad spectrum of antibiotics to treat infections caused by β-lactamase-producing pathogens. In order to evaluate the impact and the progress of CA studies in the last four decades, a bibliometric analysis of the global scientific production of CA was carried out. A total of 39,758 records in the field of CA were indexed in the Scopus database for a 43-year period of study (1975–2017). The results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…As in our study, other bibliometric studies reported that the USA ranked rst in the amount of scienti c production in resistance to other antimicrobials [19,20,22,23]. Likewise, the USA also obtained the rst place in those studies that analyzed the scienti c production of a certain drug, such as tramadol [39], aspirin [40] or clavulanic acid [17]. Given the large number of documents from the USA (n = 146), it is logical to expect them to obtain the highest number of citations (6,513).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As in our study, other bibliometric studies reported that the USA ranked rst in the amount of scienti c production in resistance to other antimicrobials [19,20,22,23]. Likewise, the USA also obtained the rst place in those studies that analyzed the scienti c production of a certain drug, such as tramadol [39], aspirin [40] or clavulanic acid [17]. Given the large number of documents from the USA (n = 146), it is logical to expect them to obtain the highest number of citations (6,513).…”
Section: Discussionsupporting
confidence: 79%
“…Previously, various drugs have been studied with bibliometric indicators [17,18], as in the case of some antiparasitics such as antimalarial drugs [19], and antifungals such as triazoles [20]. Antibiotic resistance has also been studied in a general way [21] or individually, either focusing on which organ or system is affected, such as antimicrobial resistance to uropathogens [22], or according to the class of antibiotic, for example those resistant to carbapenem [23].…”
Section: Introductionmentioning
confidence: 99%
“…β-lactam antibiotics are the most widely used class of bioactive compounds for the treatment of infectious diseases. In the last century, thousands of penicillin derivatives and related β-lactam classes of cephalosporins, cephamycins, monobactams, and carbapenems have been developed to increase the spectrum of activity of those compounds [1]. Nevertheless, the inappropriate use of commercial antibiotics, e.g., through overdoses in medical treatments and the broad use of antibiotics as growth promoters in animal husbandry, has led to the massive development of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This "antibiotic resistance crisis" is seen by the World Health Organization as one of the greatest threats to global health, food safety, and human development [2]. Resistance to β-lactam antibiotics is primarily due to the bacterial production of β-lactamase enzymes that hydrolyze the β-lactam ring, hence inactivating the drug [1].…”
Section: Introductionmentioning
confidence: 99%
“…Clavulanic acid (CA) is a soft β-lactam antibiotic with a strong inhibitory effect on β-lactamase enzymes, which confer resistance to bacteria against several known broad-spectrum antibiotics. CA is produced by the filamentous Gram-positive bacterium Streptomyces clavuligerus (S. clavuligerus) as secondary metabolite related to the clavams pathway derived from arginine and glycerol metabolism [1,2]. The Streptomyces genus is a typical source of essential antimicrobial compounds; their production is commonly carried out in liquid cultures where expression of secondary metabolite mycelia occurs [3,4].…”
Section: Introductionmentioning
confidence: 99%